Analisis Penerapan Akuntansi Lingkungan Di Rumah Sakit Mardi Waluyo Metro - Aminah AMINAH; . Noviani (Universitas Bandar Lampung (UBL), 2014)
Environmental pollution in Indonesia has reached the stage of worrying . Environment is increasingly polluted by waste from industrial activities of factories, hospitals , and hotels . This has subsequently become impulse formation Pollution Control Association (Appli) dated December 10, 2008 . Hospitals that an organization must be able to provide health insurance to the public, it is appropriate to control the waste that would have an impact on the spread of disease . Create a healthy environment should be one of the missions of organizations engaged in the field of health . So that the application of accounting and environmental management becomes an important requirement that must be done.